Potensi Minyak Jelantah Sebagai Biodiesel dan Pengaruh Katalis Serta Waktu Reaksi Terhadap Kualitas Biodiesel Melalui Proses Transesterifikasi - Muhammad Busyairi; Aufar Za’im Muttaqin; Ika Meicahyanti; Saryadi Saryadi (Fakultas Teknik, 2020)
This study aimed to determine the effect of reaction time and catalyst variations on the quality of biodiesel according to SNI 7182: 2015 determine the best reaction time and catalyst variations on the yield parameters, water content, viscosity, density, flash point, and methyl ester levels of biodiesel produced. Based on the research, the results show that the quality of biodiesel obtained for each parameter meets the SNI 7182: 2015 quality standards except for water content parameters that still exceed the quality standard limits. The best quality of biodiesel is shown in the variation of the reaction time of 120 minutes with KOH catalyst with a yield of 77.95%, moisture content of 0.2673%, density of 0.8669 gr/ml, the viscosity of 5.15 CST, flash point 174°C and levels of methyl esters 98.42%. Biodiesel from used cooking oil can be applied as renewable energy that is more environmentally efficient.This study aimed to determine the effect of reaction time and catalyst variations on the quality of biodiesel according to SNI 7182: 2015 determine the best reaction time and catalyst variations on the yield parameters, water content, viscosity, density, flash point, and methyl ester levels of biodiesel produced. Based on the research, the results show that the quality of biodiesel obtained for each parameter meets the SNI 7182: 2015 quality standards except for water content parameters that still exceed the quality standard limits. The best quality of biodiesel is shown in the variation of the reaction time of 120 minutes with KOH catalyst with a yield of 77.95%, moisture content of 0.2673%, density of 0.8669 gr/ml, the viscosity of 5.15 CST, flash point 174°C and levels of methyl esters 98.42%. Biodiesel from used cooking oil can be applied as renewable energy that is more environmentally efficient.